Editorial - Zanotelli, Claudio (Geografares, 2019)
This is the 29th issue of Geografares. This issue has different themes. Initially, two articles deal with the fruit growing theme in Espírito Santo and Minas Gerais, but from different perspectives, one analyzes the effects of climate change on plantations, the second analyzes the international fruit trade from the state of Minas Gerais. Another theme addressed in this issue is that of the economic articulations of Naviraí in Mato Grosso do Sul in the regional, national and international contexts. The fourth article deals with the spatial distribution of rainfall in the center-north of Espírito Santo. The other two articles deal with Rio de Janeiro, one analyzes, from the geography of perception, the perspectives of tourists on Ilha Grande and, the last article, deals with the ways in which the stigmatization of favelas can interfere in public policies aimed at these spaces.